(untitled) (Editora Impacto Científico, 2025)
This study analyzes the impacts of the Tamandacast project, a student-led podcast developed at the Almirante Tamandaré Full-Time School (Palmas, Tocantins), on the civic development of its participants and the school culture. The investigation is guided by the following research question: How does Tamandacast impact school culture and promote spaces for student expression and protagonism? The objective is to understand how the project contributes to civic formation, youth protagonism, and the transformation of school culture, based on the experiences of those involved. Grounded in a qualitative case study approach (Yin, 2005), the research employed semi-structured interviews and document analysis as methodological procedures to understand the perceptions of students, teachers, school administrators, and listeners regarding the project’s impact on the educational context. The results demonstrate that the project strengthens active listening (Freire, 1996), youth protagonism (Dayrell, 2003), and the collaborative production of knowledge. Furthermore, it fosters inclusion and a participatory school culture (Mantoan, 2006), aligning with the BNCC (Brazilian National Common Curricular Base) and active learning methodologies (Bacich & Moran, 2018). Tamandacast emerges as an innovative educommunication practice (Soares, 2011), with potential for social transformation and the holistic development of students. DOI: https://doi.org/10.56238/edimpacto2025.090-003